DEVELOPING A MODEL OF MULTICULTURAL SCHOOL- BASED MANAGEMENT IN SENIOR HIGH SCHOOLS IN THE FORMER PATI RESIDENCY - -, Su’ad (Universitas Negeri Semarang, 2013)
School-based management (SBM) in the era of regional autonomy has changed from centralized to decentralized school-based management (MBS). Quality disparities and narrow view of regionality are not in line withÃ‚Â the spirit of this era. Thus, there must be an effort to overcome the problem through the school-based management based on multiculturality. The goal of senior high school in the former Pati recidency in this study has referred to the regulation of the minister of education number 19 of 2007 about school management standards and implementing school Ã¢â‚¬â€œ based management (MBS). The fuction of the school management has not considered the diversity of school community, eventhough the school inputs teachers, staff, students are diverse and the school quality assurance according to the regulation of the minister of education number 63 of 2009 states that a multicultural school provides diverse education services. The identification of the problems are: 1. How is the school-based management on senior high schools in the former Pati recidency? 2. How is the development of multicultural school-based management on on senior high schools in the former Pati recidency? This dissertation uses Research and Development. In the preliminary study the writer used a qualitative approach that produced factual picture, furthermore the Ã‚Â development of the model started with the design of the model and then validated by experts and produced Ã‚Â modelÃ‚Â I then Ã‚Â it was taken to the focus group discussion (FGD) and produced model of multicultural school based management on high school in the former Pati residency. The development of multicultural school-based management on high schools in the former Pati recidency should be developed to meet the Ã‚Â goalÃ¢â‚¬â€the vision and mission of the school. The suggestions are : multicultural school-based management should be appointed as a national policy to meet the goal of a Ã‚Â school with a diversity of school community and the policy of multicultural school-based management needs to be followed up with the implementation of multicultural education in a multicultural school.